2017
DOI: 10.1021/acs.joc.7b00085
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Tandem C–H Fluoromethylation/Cyclization of N-Alkylhydrazones with CBr3F: Access to 4-Fluoropyrazoles

Abstract: 4-Fluoropyrazoles are accessible in a single step from readily available aldehyde-derived N-alkylhydrazones through double C-H fluoroalkylation with tribromofluoromethane (CBrF). RuCl(PPh) has been proven to be the most efficient catalyst for this transformation when compared to a range of other Cu-, Pd-, or Fe-based catalyst systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
(22 reference statements)
0
18
0
Order By: Relevance
“…Although it has been suggested that Drp1 does not play a role during OSKM-induced somatic cell reprogramming [114], several reports indicate that this protein plays a key role in this process [78, 115, 116]. In this regard, we have observed an increase in both Drp1 total protein and Drp1-S579 phosphorylation during the stochastic phase of cell reprogramming.…”
Section: Mitochondrial Dynamics In Cell Reprogrammingmentioning
confidence: 38%
See 4 more Smart Citations
“…Although it has been suggested that Drp1 does not play a role during OSKM-induced somatic cell reprogramming [114], several reports indicate that this protein plays a key role in this process [78, 115, 116]. In this regard, we have observed an increase in both Drp1 total protein and Drp1-S579 phosphorylation during the stochastic phase of cell reprogramming.…”
Section: Mitochondrial Dynamics In Cell Reprogrammingmentioning
confidence: 38%
“…ES cells present a fragmented mitochondrial morphology [65, 78]. Surprisingly, downregulation of growth factor erv1 -like ( Gfer ) in ES cells, which leads to an increase in Drp1 protein levels and mitochondrial fission rates, impairs pluripotency and induces apoptosis [79].…”
Section: Mitochondrial Dynamics During Embryonic Development and Cmentioning
confidence: 99%
See 3 more Smart Citations